CARE-NS, a research strategy for neurosyphilis - Du, Fang-Zhi; Zhang, Xu; Zhang, Rui-Li; Wang, Qian-Qiu (Frontiers in Medicine, 2023)
Neurosyphilis is a major clinical manifestation of syphilis. In recent years, an increase in neurosyphilis cases has been reported in many countries. The overall incidence of neurosyphilis remains unknown, and there is a lack of understanding of the disease pathogenesis, which hampers clinical management, development of prevention strategies, and control. This article proposes the CARE-NS research strategy to enhance the clinical management of neurosyphilis, which consists of six key features: comprehensive management including multidisciplinary treatment (C), alleviating neurological impairment and sequelae (A), risk factors and clinical epidemiology (R), etiology and pathogenesis (E), new diagnostic indicators and strategies (N), and social impact and cost-effectiveness analysis (S).